2019
DOI: 10.18325/jkmr.2019.29.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Ojeok-san Extract Powder and Soft Extract in Healthy Male Volunteers, Single Center, Randomized Controlled, Cross-over Study

Abstract: Objectives The purpose of this study is to evaluate the safety of Ojeok-san extract powder and soft extract in healthy male volunteers. Methods Randomized controlled, cross over study was carried out in healthy male volunteers. Total 27 of 31 subjects meeting the inclusion criteria were enrolled and three subjects for waiting were included. To each group 12 subjects were randomly allocated by random number table. Group A took the extract powder in the first period and then took the soft extract in the second p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In fact, OJS is one of the main herbal formula prescribed in Korean medical clinics to treat low back pain [ 2 , 14 ]. Experimental studies have reported analgesic, anti-pyretic, anti-inflammatory, and anti-metastatic properties of OJS with little or no-toxicity [ 15 23 ]. OJS has been shown to promote analgesia at 300 and 600 mg/kg, but not at 150 mg/kg of body weight in the pre-clinical model of acetic acid-induced arthritis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, OJS is one of the main herbal formula prescribed in Korean medical clinics to treat low back pain [ 2 , 14 ]. Experimental studies have reported analgesic, anti-pyretic, anti-inflammatory, and anti-metastatic properties of OJS with little or no-toxicity [ 15 23 ]. OJS has been shown to promote analgesia at 300 and 600 mg/kg, but not at 150 mg/kg of body weight in the pre-clinical model of acetic acid-induced arthritis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%